Platelet-Rich stroma from Crohn’s disease patients for treatment of perianal fistula shows a higher myeloid cell profile compared to non-IBD controls - J.H.C. Arkenbosch; M.A.J. Becker; C.J. Buskens; C. Witjes; A.C. de Vries; C.J. van der Woude; G. Fuhler; M.E. Wildenberg; O. van Ruler (Stem Cell Research, 2023)
Background: New cell-based therapies are under investigation to improve perianal fistulizing Crohn’s disease (pCD) healing. Autologous stromal vascular fraction combined with platelet-rich plasma (referred to as platelet-rich stroma [PRS]) is a new adipose-derived stromal therapy. The effect of Crohn’s disease (CD) on adipose tissue, and adipose-derived therapies, is largely unknown. We characterized the cellular composition of subcutaneous lipoaspirate and PRS of pCD patients and non-Inflammatory Bowel Disease (IBD) controls. Methods: Consecutive pCD patients (≥18 years) and non-IBD controls, who underwent liposuction for the purpose of autologous PRS therapy, were included (October 2020 and March 2021). Mechanically fractionated lipoaspirate and the combined PRS product were analyzed for cell surface marker expression using fluorescence-activated cell sorting analysis. Results: Twenty-three patients (37.8 [IQR 30.7–45.0] years; 9 [39.1 %] male; 11CD patients) were included. Similar total number of cells were found in CD and non-IBD lipoaspirate (CD 8.23 ± 1.62*105 cells/mL versus non-IBD 12.20 ± 3.39*105). Presence of stromal cells, endothelial like cells, immune cells, T-cells, myeloid cells and M2/M1 macrophage ratio were similar in CD and non-IBD lipoaspirate. In PRS samples, more cells/mL were seen in CD patients (P = 0.030). Myeloid cells were more abundant in CD PRS samples (P = 0.007), and appeared to have a higher regulatory M2/M1 ratio. Interdonor variation was observed between lipoaspirate and PRS samples. Conclusions: The composition of CD and non-IBD lipoaspirate were found to be similar and interdonor variation was observed. However, PRS from CD patients showed more myeloid cells with a regulatory phenotype. Crohn’s disease does not appear to alter the immunological composition of adipose-derived products.